The Influence Of The Use Of Social Media In The Workplace On Employee Performance By Considering The Mediation Role Of Social Capital And Knowledge Transfer - Bornin Medan, Ridski; Yusuf, Furtasan Ali (Center of Language and Cultural Studies, 2024)
Nowadays, social media is not only used for personal or social relationships. However, it has been widely used for work purposes, namely communicating, collaborating, exchanging information and sharing knowledge. However, there are only a few studies that discuss the relationship between the use of social media in the workplace and employee performance in the government sector. Specifically, this research aims to identify the influence of social media use on employee performance through its impact on social capital and knowledge sharing in the government sector. This research uses quantitative methods with analysis structural equation modelling partial least square (SEM-PLS) with a sample of 109 non-ASN employees at BPKAD Serang City and BPKAD Serang Regency. The research results prove that there is a significant influence in the direction of a positive relationship between the use of social media in the workplace and social capital. There is no influence from the use of social media in the workplace on employee performance. There is a significant influence in the direction of a positive relationship between the use of social media in the workplace and knowledge transfer. There is a significant influence in the direction of a positive relationship between social capital and employee performance. There is a significant influence in the direction of a positive relationship between knowledge transfer and employee performance.